Influence of different isolation methods on physicochemical and rheological properties of native and heat‐moisture‐treated chickpea starch. Issue 2 (19th November 2017) - Singh, Sumit; Thakur, Sheetal; Singh, Monu; Kumar, Ankit; Kumar, Amit; Kumar, Akhilesh; Punia, Rakesh; Kushwaha, Jyoti; Kumar, Rajendra; Singh, Harinder
Abstract: Starch from chickpea seeds was isolated using three different steeping solutions viz water, sodium hydroxide and potassium metabisulfite and subsequently heat‐moisture treated (HMT) at 110 °C after adjusting moisture contents to 30% for 8 hr. The aim was to see the effect of steeping solutions on the physicochemical, morphological, crystalline and rheological properties of chickpea starch and their influence on heat‐moisture treatment of the starches. Starch isolated by water as steeping media showed the highest amylose content and swelling power. HMT starches showed lower granule sizes, swelling power, and bulk and tapped densities than native starch. The X‐ray diffraction pattern of HMT starches also showed difference in position and intensity of peaks. The starches after heat‐moisture treatment also differed significantly in loss and elastic modulus than those of native starches. Practical applications: There is increased demand of heat‐moisture treated starches by the food industry. The present research is aimed at finding the isolation method of starch from chick pea seeds which can be subsequently used for heat‐moisture treatment. This can help industry to selectively modify the process before physical modification. There is a need of more understanding of how starch behaves after heat‐moisture treatment and its possible uses in products as texture stabilizer, and this research is directed at achieving at these aims.